The factors that influence people to join martial arts : A case study among the martial arts practitioners at Persatuan Seni Silat Cekak Pusaka Ustaz Hanafi / Muhammad Mu’izzuddin Mohd Hatta and Nursakinah Salim - Mohd Hatta, Muhammad Mu’izzuddin; Salim, Nursakinah (Faculty of Administrative Science and Policy Studies, 2014)
Martial arts are one form of defensive technique. Martial arts have become one of the most popular physical activities amongst children and youth worldwide. Martial arts also can give benefit to the people who joining it with good psychology, health and psychosocial. But there are several scholars and studies that oppose martial arts will increase the level of aggressiveness and violence among the practitioners. This study will examine the factors that influence people to join martial arts. What is the most influencing factor that attracts people to join martial arts.